2018
DOI: 10.3168/jds.2017-13868
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Probiotic induction of interleukin-10 and interleukin-12 production by macrophages is modulated by co-stimulation with microbial components

Abstract: Probiotic lactobacilli stimulate macrophages and dendritic cells to secrete cytokines and thereby regulate the immune responses of the host. The balance of the IL-10 and IL-12 production induced by a probiotic is crucial for determining the direction of the immune response. In the present study, we examined the ability of microbial components to modify IL-10 and IL-12 production induced by a popular probiotic strain, Lactobacillus casei strain Shirota (LcS), which itself predominantly induces IL-12 production.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 16 publications
0
22
0
1
Order By: Relevance
“…It is recognized that cellular components derived from probiotics interact via PRRs, including NOD-like receptors and the family of TLRs, which can modulate cytokine production [59]. It has been reported that TLR2 is involved in the secretion of both pro-and anti-inflammatory cytokines in response to probiotic strains [60,61]. We demonstrated that the mechanism responsible for macrophage activation by heat-killed probiotic bacteria is TLR2-dependent, blocking antibody treatments and showing that L. casei IMAU60214 acted as a TLR2 agonist in macrophages, in accordance with a recent investigation demonstrating immune regulation through TLR2/TLR6 signaling in response to LAB [62].…”
Section: Discussionmentioning
confidence: 99%
“…It is recognized that cellular components derived from probiotics interact via PRRs, including NOD-like receptors and the family of TLRs, which can modulate cytokine production [59]. It has been reported that TLR2 is involved in the secretion of both pro-and anti-inflammatory cytokines in response to probiotic strains [60,61]. We demonstrated that the mechanism responsible for macrophage activation by heat-killed probiotic bacteria is TLR2-dependent, blocking antibody treatments and showing that L. casei IMAU60214 acted as a TLR2 agonist in macrophages, in accordance with a recent investigation demonstrating immune regulation through TLR2/TLR6 signaling in response to LAB [62].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, TGFB1 expression has been related to immunological tolerance towards microbial compounds, including short-chain fatty acids, lactic acid, surface proteins of lactobacilli, peptidoglycan-derived neuropeptides, and histamine (Kashiwagi et al, 2015;Bauché and Marie, 2017;Ihara et al, 2017). Accordingly, decreasing jejunal IL8 and IL10 expression might be associated with the DON-related decreased TLR2 expression and thus with changes in the microbiota composition (Cotton et al, 2016;Kaji et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…(2020) 10:2926 | https://doi.org/10.1038/s41598-020-59756-z www.nature.com/scientificreports www.nature.com/scientificreports/ Kaji et al 66 have shown that bacterial ligands for Tlr2, Tlr4, and Tlr9 may convert the cytokine production pattern from predominantly pro-inflammatory to anti-inflammatory, indicating that probiotic induction of pro-and anti-inflammatory cytokines can be modified by co-stimulation with microbial components; an effect that has also been observed in monocytes 67 and in dendritic cells 68 . The kind of response (either pro-or anti-inflammatory) further depends on TLR compartmentalization in the cell.…”
Section: Scientific Reports |mentioning
confidence: 99%